Chronic Kidney Disease, Metabolic Syndrome, and Cardiovascular Risk: Insights and Associated Mechanistic Pathways - Nogueira, Thaís R.; Marreiros, Camila Santos; de Jesus e Silva de Almendra Freitas, Betânia (Current Nutrition & Food Science, 2022)
This study is a narrative review that aims to address the conceptual, characteristic, pathophysiological, and mechanistic aspects that define the profile of metabolic syndrome and chronic kidney disease. The objective was to investigate current knowledge and elucidate, through discussions on the topic, the main interrelated paths. This review was carried out unsystematically, from March to May 2020, by means of a survey of the literature indexed in the PubMed, Web of Science, and Scopus (Elsevier®) databases. The scientific materials collected showed that the cross-talk between the diseases in question is mainly based on the conditions of resistance to insulin action, endothelial dysfunction, activation pathways of the Renin- Angiotensin-Aldosterone System, and adipokine imbalance, also emphasizing the influence of atherosclerotic events in kidney damage. Furthermore, it was reinforced that inflammatory processes play an important role in the worsening and evolution of the clinical condition of patients, especially when they have underlying pathologies chronically treated for subclinical inflammation. It is expected that more original research will propose investigating other possible interactions with a view to standardized treatment of these diseases or nutritional management.
Keywords: metabolic syndrome